TAFSIR LINGUISTIK BINTU SYATHI’ - Choiroh, Wahyuni Nuryatul (Program Studi Ilmu Al-Quran dan Tafsir Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2023)
This paper will discuss conceptually the literary method of Amin al-Khulli applied by Bintu Syathi' in interpreting the Qur'an. Amin al-Khulli himself never published a book of Tafsir, it's just that his book Manahij al-Tajdid often became a reference for later commentators. This paper discusses the urgency and relevance of the linguistic approach to the interpretation of the Qur'an, by reviewing the book of al-Tafsir al-Bayani li al-Qur'an al-Karim by Bintu Syathi' as an implementation of al-Tafsir al-Lughawi which is a roots of the methodology of Amin al-Khulli's ideas. This paper proves that understanding the methods and linguistics of language is the main requirement in capturing the message of the Qur’an. As one of the methods of interpretation that is ijtihadi, using a language approach to the interpretation of the Qur'an will certainly not escape its advantages and disadvantages. Although Bintu Syathi' thoughts cannot be separated from controversial debates in applying her husband's rules, Bintu Syathi's interpretation is a brave effort and provides fresh air in the development of interpretation in modern times.